The Involvement of Father in Child Development: A Theoretical Research Progress - Hou , Yongmei (Recent Trends in Arts and Social Studies Vol. 8, 2023)
Background: In recent years, with the development of social economy, the problem of father's participation in parenting in family education has become increasingly prominent, which is mainly manifested in the following aspects: father's participation in children's parenting is less time, father's participation in parenting styles tends to be more "introverted", and father's absence in parenting affects children's development. There has been a lot of research in the academic community on the reasons for this issue, but a consensus has not been reached: some scholars analyze objective factors and believe that it is due to the influence of the traditional concept of "male dominated outside, female dominated inside", and in the real environment, high work pressure, employment in other places, divorce and separation, etc., which leads to fathers being unable to raise children. Other scholars analyze subjective factors, and think the main reason is that fathers lack awareness of raising children and professional parenting knowledge. Scholars have varying opinions on strategies to increase father participation: some advocate establishing a comprehensive mechanism for ensuring access to education in different regions at the societal level; some people suggest legislating from a legal and policy perspective to provide fathers with sufficient leave to accompany their children; some people believe that attention should be paid to cultivating parents' awareness of participating in raising children; some people point out the need to abandon the constraints of traditional thinking at the family level, learn professional parenting knowledge through multiple channels, communicate well at the school level, provide assistance for fathers to raise children, and carry out various forms of activities to encourage fathers to participate. In summary, it can be seen that "father involvement" is a concept with rich content and complex structure, and its connotation has strong cultural dependence. Methods and Content: This paper uses the document retrieval method to systematically sort out the theoretical research literature on father’sinvolvement at home and abroad, comprehensively introduce the concept, practical significance and theoretical basis of father’sinvolvement, describe nine theories about its content structure, present the differences of opinion, analyze the current research situation and existing problems, and point out the development direction of the research. Conclusion: Father’sinvolvement is a complex social problem, which involves not only pedagogy and psychology, but also sociology, philosophy, management, medicine, sports kinematics and other disciplines. We need to carry out cross disciplinary research from multiple fields and perspectives, strengthen experimental and follow-up research with large samples and multiple centers, and deeply explore the connotation, composition, influencing factors, and mechanism of father’sinvolvement, in order to correctly understand the essence of "father's involvement" and reasonably guide its development.